2015
DOI: 10.1111/lest.12094
|View full text |Cite
|
Sign up to set email alerts
|

Autonomy, capacity and vulnerable adults: filling the gaps in the Mental Capacity Act

Abstract: This paper explores the distinction between being autonomous and having capacity for the purposes of the Mental Capacity Act. These include where a person misuses affective attitudes in making the decision; where a person's decision is not authentic to their values; and where the Mental Capacity Act prevents use of the context or outcome of the decision in assessing capacity. These gaps mean that a person can be found to have capacity, even though they are not properly autonomous. This, we argue, justifies the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 3 publications
0
18
0
2
Order By: Relevance
“…Typically, the evolution of law and practice in seen as defensible only when it shifts along this spectrum, endorsing consent practices that equate with a more patient-centred and autonomyfocused approach. One point that we have endeavoured to clarify in this paper is that, as with other areas of health care practice and research, 1 patient-centrism does not, and need not, track the value of individual patient autonomy within the doctor-patient relationship, in general, and with regards to the framing and articulation of norms of information disclosure, in particular [16].…”
Section: The Moral Terrain Of Informed Consent Within the Doctor-patimentioning
confidence: 95%
“…Typically, the evolution of law and practice in seen as defensible only when it shifts along this spectrum, endorsing consent practices that equate with a more patient-centred and autonomyfocused approach. One point that we have endeavoured to clarify in this paper is that, as with other areas of health care practice and research, 1 patient-centrism does not, and need not, track the value of individual patient autonomy within the doctor-patient relationship, in general, and with regards to the framing and articulation of norms of information disclosure, in particular [16].…”
Section: The Moral Terrain Of Informed Consent Within the Doctor-patimentioning
confidence: 95%
“…Indeed emotions used to be regarded as in competition with reason. People who were 'emotional' were of doubtful capacity (for example, Re MB [1997] EWCA 1361) and legal reasoning had to be based on cold rationality (Herring and Wall, 2015). There are a number of problems with such an approach.…”
Section: Emotions Are Ethically and Practically Significantmentioning
confidence: 99%
“…Such a manoeuvre was largely welcomed by commentators who had noted that autonomy had been inadequately protected by the Mental Capacity Act 2005 (e.g. Herring and Wall, 2015). It was not until a year later, however, that Justice Munby sought to elaborate the foundations of the jurisdiction more clearly when he concluded that he had authority to use the High Court's jurisdiction in order to protect a profoundly hearing-impaired young woman with a learning disability (Re SA [2005]).…”
Section: Filling the Gapthe Vulnerable Adults Jurisdictionmentioning
confidence: 99%